THE EFFECT OF LEADERSHIP, ORGANIZATION CULTURE AND MOTIVATION TO THE PERFORMANCE OF EMPLOYEES AT OFFICE OF COOPERATIVES, SMALL AND MEDIUM ENTERPRISES AND TRADE KABUPATEN DHAMASRAYA - ., Muchli Endri Yose; Heryanto (Archives of Business Research, 2019)
This research aimed to analyze the effect of Leadership, Organization Culture and Motivation to the performance of employees at Office Of Cooperatives, Small And Medium Enterprises And Trade Regency Of Dharmasraya. This research used primary data which were obtained by distributing questionnaires to the employees at Office Of Cooperatives, Small And Medium Enterprises And Trade. The Technique of sampling used in this research was convenience sampling. There are 37 samples in this research. Technique of data analysis was multiple regression. The result of the research shows that leadership, motivation, work disciplines, competency and organization culture have significant effects to the performance of the employees.